The enhancement of victim empathy among incarcerated child molesters - Marshall, William L. (Legal and criminological psychology, 1996)
A treatment component aimed at enhancing empathy among child molesters is described and evaluated using a victim-specific measure of empathy. Twenty-nine non-familial child molesters were assessed prior to and immediately after this treatment component. The results revealed a significant improvement in the offenders' scores on the measure of their empathy toward their own victims and in their reports of their own feelings of distress concerning victims of child abuse in general.